Ophthalmologic evaluation in geriatric patients: Assessment of consistency between patients' complaints and ocular diagnoses. (January 2017) - Yakin, Mehmet; Yalniz-Akkaya, Zuleyha; Sevim-Yakin, Sultan; Balta, Ozgur; Ornek, Firdevs
Highlights: With age the prevalence of visual impairment increases. A significant proportion of the patients are unaware of their ocular diseases. Cataract, glaucoma and ARM are the leading causes of visual impairment. The first study evaluating the consistency between complaints and ocular diseases Abstract: Purpose: This study aimed to assess the consistency between patients' complaints and their eye diseases. Design: Cross-sectional study. Methods: Setting: Institutional. Study population: 1084 eyes of 544 elderly (≥65 years) patients. Observation procedure: The eyes of the patients who had only ocular surface complaints were classified as group 1, those who wanted to renew their glasses and had no other complaints were classified as group 2, and those who complained about decrease in vision were classified as group 3. Main outcome measures: Frequency of visual impairment and visually important ocular diseases. Results: The frequencies of at least one newly diagnosed visually important ocular disease were 25.9%, 27.0%, and 45.3% in groups 1, 2, and 3, respectively (p < 0.001). The same frequencies were significantly higher in patients >75 years of age compared with the younger group (59.1% vs. 22.0%, p < 0.001). Although these values were statistically significant in patients ≤75 years of age (p < 0.001), they were insignificant in patients >75 years of age according to type of complaints (p = 0.773). Patients with diabetes mellitus exhibited significantly lower vision, higher rate of visually important ocular diseases, and higher intraocular pressure readings than patients without diabetes mellitus (p = 0.009, 0.015, and 0.002, respectively). Conclusions: Visually important ocular diseases were diagnosed approximately in a quarter of patients who had no complaints about decrease in vision and in more than half of the oldest geriatric patients ( > 75 years) irrespective of the type of complaints.